2008
DOI: 10.2196/jmir.1008
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Internet Assistance for Smoking Cessation: 13-Month Follow-Up of a Six-Arm Randomized Controlled Trial

Abstract: Background Although many smokers seek Internet-based cessation assistance, few studies have experimentally evaluated long-term cessation rates among cigarette smokers who receive Internet assistance in quitting.Objective The purpose of this study is to describe long-term smoking cessation rates associated with 6 different Internet-based cessation services and the variation among them, to test the hypothesis that interactive and tailored Internet services yield higher long-term quit rates than more static Web-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 18 publications
1
74
2
3
Order By: Relevance
“…Also, it was not feasible to biochemically verify self-reported abstinence since this was a national sample recruited via the Internet. Self-reported abstinence is commonly accepted in web-based cessation trials (Leykin, Aguilera, Torres, Pérez-Stable, & Muñoz, 2012;Rabius, Pike, Wiatrek, & McAlister, 2008;Strecher et al, 2008;Wangberg, Nilsen, Antypas, & Gram, 2011;Zbikowski, Hapgood, Smucker Barnwell, & McAfee, 2008) where misreporting of abstinence is expected to be minimal (SRNT Subcommittee on Biochemical Verification, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was not feasible to biochemically verify self-reported abstinence since this was a national sample recruited via the Internet. Self-reported abstinence is commonly accepted in web-based cessation trials (Leykin, Aguilera, Torres, Pérez-Stable, & Muñoz, 2012;Rabius, Pike, Wiatrek, & McAlister, 2008;Strecher et al, 2008;Wangberg, Nilsen, Antypas, & Gram, 2011;Zbikowski, Hapgood, Smucker Barnwell, & McAfee, 2008) where misreporting of abstinence is expected to be minimal (SRNT Subcommittee on Biochemical Verification, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, research has found that therapies without client contact are at risk of high levels of drop-out (Christensen, Griffiths, Mackinnon, & Brittliffe, 2006;Farvolden, Denisoff, Selby, Bagby, & Rudy, 2005;Rabius, Pike, Wiatrek & McAlister, 2008). It is to this issue that Hyland's (2010a, 2010b) finding that people are less likely to drop out of a gratitude technique than one from classical clinical psychology becomes important.…”
Section: Symptoms Of Psychological Disordermentioning
confidence: 99%
“…Self-reported smoking status is a commonly accepted outcome measure in Internet cessation trials, 12,[22][23][24][25][26][27] where biochemical verification of abstinence is not feasible and misreporting of abstinence is expected to be minimal given low demand characteristics.…”
Section: Primary Outcomementioning
confidence: 99%
“…10 Smoking variables that have emerged as moderators in web-based studies include baseline smoking rate, 11 the presence of a tobacco-related illness, 5 nonsmoking children in the household, 5 and intention to stop smoking. 10 Psychosocial moderators that have emerged in other studies include depressive symptoms, 12 a history of major depressive episodes, 13 and frequent alcohol consumption. 5 We sought to build on the limited evidence in this area by examining theory-driven mediators and moderators of treatment effectiveness in The iQUITT Study (Quit Using Internet and Telephone Treatment), a randomized controlled trial of Internet and telephone treatment for smoking cessation.…”
Section: Introductionmentioning
confidence: 99%